The Epidemiology of Needle Stick and Sharp Injuries in Central Sterile Supply Department of Hospitals in Hunan Province, China - Lin, XIAO; Qing-yan, WANG; Hong, KANG; Si-yuan, TANG (International Journal of Infection Control, 2014)
Objective: The aim of this descriptive study was to determine the prevalence and explore the potential risk factors of Needle Stick and Sharps Injuries (NSSIs) among nurses and nursing assistants in central sterile supply department (CSSD) of Hunan hospitals, China. Methods: This cross-sectional study was conducted in Hunan province, China. Sample of the study comprised 247nurses and 95 nursing assistants. Data were collected using a semi- structured questionnaire developed by researchers. Result: Of the 342 participants interviewed, 304 (88.9%) and 288 (84.2%) were exposed to at least one NSSI in their lifetime and in the previous year, respectively, with a total of 431 self–reported NSSIs having occurred during the previous 12 months. Those who were registered nurses (OR 0.313), reported after exposure (OR 0.292), thought of NSSIs avoidable (OR 0.442), received more sources of occupational safety knowledge (OR 0.451) and by whose hospitals preventive measures adopted (OR 0.731) had lower risk of sustaining a NSSIs. While those who worked in high noise level environment (OR 1.649) and contacted sharps frequently (OR 1.388) had more probability of having an injury. Conclusion: This study shows that a significant percentage of nurses and nursing assistants in CSSD receive NSSIs. Prevention of occupational infection requires a comprehensive approach to reduce exposure and provide pre-exposure and post-exposure prophylaxis for NSSIs.